2017
DOI: 10.1007/s10554-017-1230-z
|View full text |Cite
|
Sign up to set email alerts
|

New echocardiographic parameters in the diagnosis of heart failure with preserved ejection fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a serious clinical disease. The pathophysiology of HFpEF is complex, and specific diagnostic criteria have evolved over time. Limited data are available on the quantification of diastolic function using two-dimensional real-time echocardiography, and a simple parameter has not yet been established. The aim of this work is to evaluate new echocardiographic parameters-the diastolic wall strain of the posterior wall (DWS PW) and the vortex formation time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This study corroborates those ndings for pediatric HTN, indicating that adolescents with HTN display signi cantly lower VFT than adolescents without HTN. These ndings also provide support for previous studies which have observed lower VFT values in adult patients with diastolic dysfunction, as adolescents with higher SBP displayed lower VFT [26,31,32].…”
Section: Discussionsupporting
confidence: 90%
“…This study corroborates those ndings for pediatric HTN, indicating that adolescents with HTN display signi cantly lower VFT than adolescents without HTN. These ndings also provide support for previous studies which have observed lower VFT values in adult patients with diastolic dysfunction, as adolescents with higher SBP displayed lower VFT [26,31,32].…”
Section: Discussionsupporting
confidence: 90%
“…In the normal heart, the vortex is responsible for entering about 13% the filling volume, while this portion is reduced to 5% in hypertrophic cardiomyopathy 27 . Impaired generation of this swirling structure has also been shown in HFpEF, 28 and perturbation of the vortex function has been associated with increased cardiovascular mortality and rehospitalization 29 . Biomechanical models of the left ventricle have visualized that the regurgitant jet of mild or moderate AR impedes vortex formation as a function of its severity, 30 suggesting that already a small regurgitant volume should worsen the pre‐existing pathologic vortex formation in patients with preserved LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, >70% of patients with CHF aged >65 years have a preserved LVEF (HFpEF), and this proportion tends to increase together with the rising prevalence of associated underlying health conditions (obesity, metabolic syndrome, and diabetes mellitus) [10]. In contrast to CHF with a reduced (<50%) LVEF (HFrEF), which progression can be directly assessed in a noninvasive manner by echocardiography, efficient monitoring of the cardiac status in the patients with HFpEF is challenging [11], although a number of studies in this direction have been reported [12,13]. Taken together, these facts underscore the importance of finding the informative and routinely measurable biomarkers of ventricular remodeling in this patient category [14].…”
Section: Introductionmentioning
confidence: 99%